2017
DOI: 10.18203/2320-1770.ijrcog20175846
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication of abortion pills and its complications: an observational study

Abstract: Background: Medical termination of pregnancy has been legalized in India since 1971. Medical abortion pill is well effective in early weeks of pregnancy. It is safe only when it is used under medical supervision. This study was carried out to analyse the complications following self-medication of abortion pills and to suggest measures to prevent such practice.Methods: This was a retrospective observational study conducted at our hospital from March 2017 to July 2017.Results: In present study 30 (75%) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…The overall risk of developing ectopic pregnancy by over the counter abortificient is as high up to 1.9% to 6.5%. 24,25 In this study, another risk factor, previous ectopic pregnancy was 4.5% which is similar to studies by Ansa et al (4.4%), 26 Hussam et al (4.7%), 27 Shraddha et al (3.2%) 21 , Anita et al (5.4%) 13 and Rajendra et al (5.7%). 17 This is most likely due to tubal factors that are usually bilateral.…”
Section: Discussionsupporting
confidence: 89%
“…The overall risk of developing ectopic pregnancy by over the counter abortificient is as high up to 1.9% to 6.5%. 24,25 In this study, another risk factor, previous ectopic pregnancy was 4.5% which is similar to studies by Ansa et al (4.4%), 26 Hussam et al (4.7%), 27 Shraddha et al (3.2%) 21 , Anita et al (5.4%) 13 and Rajendra et al (5.7%). 17 This is most likely due to tubal factors that are usually bilateral.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study maximum cases 21 (77%) were married but were not prepared for a child and were open to resorts like over the counter medical abortifacients for easy solution. It was comparable to other studies conducted by Thaker et al, Agarwal et al and Munshi et al (2018). This shows that abortion pills rather than being used for indicated indications that are given under MTP act is being used as a substitute for contraception by the age group of high fertility and reproductive potential.…”
Section: Marital Statussupporting
confidence: 88%
“…Abortion is a willful termination of pregnancy beyond period of viability. 1 Medical abortion is defined by World health organization as "Usage of pharmacological drugs to terminate pregnancy. 2 World health organization defines unsafe abortion as a procedure for terminating an unwanted pregnancy either by persons lacking the necessary skills or in environment lacking minimal medical standards or both.…”
Section: Introductionmentioning
confidence: 99%
“…Munshi et al reported that majority of women 30 (75%) had consumed the abortion pills 1-10 days before coming to the hospital. 13 In present study, it was found that 29% of participants herself brought the medicines from chemists, 36.7% of patients husbands brought medicines and 34.3% of patients' other relatives brought medicines. Thakur et al reported that source of information regarding pills was Husband (28.57%) in most of the cases, followed by chemist, friend or relatives (14% each).…”
Section: Discussionmentioning
confidence: 51%